2021
DOI: 10.1093/jas/skab228
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory feeding during early gestation for sows with a high weight loss after a summer lactation increased piglet birth weight but reduced litter size

Abstract: Sows mated in summer produce a greater proportion of born-light piglets (<1.1 kg) which contributes to increased carcass fatness in the progeny population. The reasons for the low birth weight of these piglets remain unclear, and there have been few successful mitigation strategies identified. We hypothesized that: (1) the low birth weight of progeny born to sows mated in summer may be associated with weight loss during the previous summer lactation; and (2) increasing early gestation feed allowance for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Table 8 lists the main conclusions of some studies on the effect of light time on milk yield and weight loss of multiparous sows. The results showed that there was no significant difference in prolactin concentration, milk composition and colostrum intake of multiparous sows under the light time of 8, 16 and 23 h during lactation, but their feed intake and weight loss were reduced under the light time of 16 and 23 h (Dimitrov et al, 2018; Lachance et al, 2010; Liu, Braden, et al, 2021; Liu, Song, et al, 2021; Mabry et al, 1982). Meanwhile, the lactation number of multiparous sows, as well as the number and weight of weaned piglets under 16 h light were more than those under 8 h light (Kraeling et al, 1987; McGlone, Stansbury, & Tribble, 1988; McGlone, Stansbury, Tribble, & Morrow, 1988; Sevillano et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 8 lists the main conclusions of some studies on the effect of light time on milk yield and weight loss of multiparous sows. The results showed that there was no significant difference in prolactin concentration, milk composition and colostrum intake of multiparous sows under the light time of 8, 16 and 23 h during lactation, but their feed intake and weight loss were reduced under the light time of 16 and 23 h (Dimitrov et al, 2018; Lachance et al, 2010; Liu, Braden, et al, 2021; Liu, Song, et al, 2021; Mabry et al, 1982). Meanwhile, the lactation number of multiparous sows, as well as the number and weight of weaned piglets under 16 h light were more than those under 8 h light (Kraeling et al, 1987; McGlone, Stansbury, & Tribble, 1988; McGlone, Stansbury, Tribble, & Morrow, 1988; Sevillano et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, some scholars found that precise feeding can partially improve the feed intake, physiological indexes and reproductive performance of lactating sows under heat stress, and their main conclusions are shown in Table 5. According to Table 5, compared with the standard gestation feeding regime (2.6 kg/day), the weight loss of lactating sows during lactation and their back‐fat thickness loss were reduced under high temperature when the gestation feeding regime with 3.5–4.3 kg/day was adopted during their early pregnancy (Carrión‐López et al, 2022; Gianluppi et al, 2020; Liu, Braden, et al, 2021). However, there was no significant difference in their litter size and foetal viability rate (Carrión‐López et al, 2022; Gianluppi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%